Przyczyny i konsekwencje rozbieżności rozumienia przymiotu nierozerwalności małżeńskiej w prawosławiu i katolicyzmie - Bartosz Trojanowski (Polonia Sacra)
The proposed topic is extremely timely in an era of debate over the possibility of allowing divorced persons who have remarried to receive Holy Communion. In this regard it is worth examining the causes and consequences, which are still present in the canon of the Catholic Church, with a different understanding of the attribute of marital indissolubility. While in fact the Catholic Church and the Orthodox Church agree on the teaching of the sacraments, including the teaching of the sacrament of marriage and its attribute of indissolubility, in practice the understanding of indissolubility results in a different use of canon in both Churches. The reason is primarily a different interpretation of the so-called Matthew clause. Hence, in the East, St. Basil the Great in some way allowed the practice of penance for divorced people who remarried. While his teaching on marital indissolubility is clear, the same cannot be said for the explanation of the discipline he recognizes. Interpretation of the individual principles described by St. Basil, causes many difficulties. In the West, the most significant Church Father in this matter is St. Augustine, he synthesized the teaching on marriage while explaining the doctrine and practice to be followed. He did not omit the attribute of indissolubility and defined the relationship between a man and a woman before the end of the previous marriage as adultery. As a consequence of the differences in understanding of the attribute of marital indissolubility, there are clear restrictions in today’s canonical discipline in the Catholic Church, which must be observed in the case of some pastoral service towards an Orthodox person, whether in the case of a mixed marriage or for any other reason.